Analysis and Determination of early warning index for Mountain Flood Disasters—A Case Study of Yalin River Small Watershed. Issue 1 (March 2020) - Zheng, Shi; Lin-lin, Hu; Huan-Bao, Chen; Hong-xia, Tang
Abstract: Determination of the critical rainfall is very important for the influence by mountain torrents with disaster prevention and reduction in significance, which is the priority among priorities of mountain flood early warning work. In this paper, the small watershed of Yalin River as the example, has carried on the analysis and the calculation of flood disaster early warning index. The results show that, the using method is simple and practical, with the certain reference value to the mountain torrent disaster warning.